Managing projects with Microsoft Visual studio team system - Semeniuk, Joel (Microsoft Press, 2007)
This book is a practical guide to using the integrated tools in Visual Studio Team System to manage a team-development process. Project managers typically use a wide range of tools—such as Microsoft Office Excel®, Microsoft Office Project, and Microsoft Windows® SharePoint® Services. The Visual Studio Project Management Tools are integrated with the Visual Studio integrated development environment (IDE), Office, Windows SharePoint Services, and Microsoft SQL Server™ 2005 Reporting Services. This helps enable project managers to continue using the tools with which they are comfortable, yet easily share their development-oriented project data with their teams—allowing architects, developers, testers, and project managers to collaborate in a single, extensible environment. With in-depth product information and insights from early users and experienced Visual Studio Team System trainers, this guide will help you understand how to use this tightly integrated set of life-cycle development tools to help enable better planning, scheduling, collaboration, communication, reporting, and process control with development projects.